Enhancing production efficiency through optimizing plant density in maize–soybean strip intercropping - Li, Guanghao; Liang, Yuwen; Liu, Qiannan; Zeng, Jinghan; Ren, Qingming; Guo, Jian; Xiong, Fei; Lu, Dalei (Frontiers in Plant Science, 2024)
Due to limited arable land resources, intercropping has become an efficient and sustainable production method to increase total grain yield per unit land area. Maize-soybean strip intercropping (MSSI) technology is being widely promoted and applied nationwide in China.However, the combination of optimal density for achieving higher production efficiency of soybean and maize remain unclear. The objective of this study was to evaluate the differences of yield, economic benefits, land and nitrogen (N) efficiency in MSSI system under different density.Five maize/soybean density combinations (67500/97500 plants ha -1 , D1; 67500/120000 plants ha -1 , D2; 67500/142500 plants ha -1 , D3; 60000/142500 plants ha -1 , D4; 52500/142500 plants ha -1 , D5) were set under the same N input in the field experiment. The results demonstrated that optimizing the density in intercropping system could enhance production efficiency. Increasing the density of soybean and maize significantly increased the total grain yield (D3>D2>D1>D4>D5). The D3 with the best comprehensive performance promoted the increase of leaf area index, dry matter accumulation, N absorption and utilization. Path analysis indicated that density had the most substantial impact on maize yield, while grain number had the greatest influence on soybean yield, and the contribution rates to yield were 49.7% and 61.0%, respectively. Therefore, the results provide a more valuable field density for the summer planting area of MSSI, thus facilitating the wider adoption of this mode.